2011
DOI: 10.1002/app.34445
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selected photoinitiators on important properties of photoreactive acrylic pressure‐sensitive adhesives

Abstract: Photoreactive solvent-borne pressure-sensitive adhesives are not commercially available in the market. The reason for it is that the UV-initiated crosslinking has sense only in the case of solvent-free self-adhesive systems. Investigations conducted in Institute of Chemical Organic Technology have shown that the photoreactive solvent-borne acrylic PSA are conventional crosslinked solvent-borne acrylic PSA used as crosslinking agents typical metal chelates as titanium acetylacetonate (TiACA), aluminum acetylace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
0
21
0
3
Order By: Relevance
“…Two release films not containing OCA were used for baseline correction, which was equal to 100%. The measured transmittances of the acrylic PSAs are above 100%, indicating that the acrylic PSA-coated PET films exhibit better transparency than that of the neat films support [19].…”
Section: Uv-visible Spectroscopymentioning
confidence: 96%
See 1 more Smart Citation
“…Two release films not containing OCA were used for baseline correction, which was equal to 100%. The measured transmittances of the acrylic PSAs are above 100%, indicating that the acrylic PSA-coated PET films exhibit better transparency than that of the neat films support [19].…”
Section: Uv-visible Spectroscopymentioning
confidence: 96%
“…The black light (BL) lamp, which provides very weak UV light energy, is also employed for primary curing. In general, the properties of acrylic PSAs vary according to the mechanical and chemical methods employed, e.g., adjusting the amount or type of blended tackifiers, the extent of the main chain cross-linkage [18], and also the type of cross-linking system [19]. Therefore, it is important to understand the differences in the chemical and physical properties of the system, and the possibility of complete curing when the crosslinking process is divided into two steps.…”
Section: Introductionmentioning
confidence: 99%
“…Photo-crosslinking PSA systems are essentially room-temperature crosslinking which makes it to crosslink the high temperature coating systems including calendaring and hot-melt coating where the use of conventional thermal crosslinking technology is typically denied. [17] Over the last 25 years, photocrosslinking science and technology has grown from a subject of esoteric research specialties into a major industrial development and is now a field of the central importance in polymer science and technology. [18][19][20] However, the fundamentals on the selection of photoinitiators for diverse applications should be systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The cross‐linking state is also important, and there are various kinds of cross‐linkers for PSAs. Multifunctional epoxy and isocyanate compounds are generally used as cross‐linkers in industrial acryl‐based PSAs, and they form irreversible covalent bonds . On the other hand, it has been reported that chemical units for noncovalent interactions were incorporated into a soft material to change the properties of the bulk by temporal cross‐linking .…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional epoxy and isocyanate compounds are generally used as cross-linkers in industrial acryl-based PSAs, and they form irreversible covalent bonds. 11,12 On the other hand, it has been reported that chemical units for noncovalent interactions were incorporated into a soft material to change the properties of the bulk by temporal cross-linking. [13][14][15] These units were introduced at side chains or termini of main chains to form reversible polymer networks.…”
mentioning
confidence: 99%